Daniel Martin - John Fowles (Boston, MA A Signet Book, 1977)
Set internationally and spanning three decades, Daniel Martin is, among other things, an exploration of what it is to be English. Daniel is a screenwriter working in Hollywood, who finds himself dissatisfied with his career and with the person he has become. In a richly evoked narrative, Daniel travels home to reconcile with a dying friend, and also to visit his own forgotten past in an attempt to discover himself.
Keywords: Fiction; Classics; Philosophy